ANALISIS DAN PENERAPAN DATA MINING UNTUK MENENTUKAN GAJI KARYAWAN TETAP DAN KARYAWAN KONTRAK MENGGUNAKAN ALGORITMA K-MEANS CLUSTERING - Novi Yona Sidratul Munti (Universitas Pahlawan Tuanku Tambusai, 2018)
The company is a unit of production activities that cultivate economic resources to provide goods and services for society with the aim of gaining profit and satisfy the needs of the community. Within the company we need to determine the classification of a worker for the purpose of assessing propesionalismeemployess ,in order to improve the quality ofworkers in a company.Search employee’s salary is still done manually, so there are still many in receipt of a salary, so that led to some employees complained upon receipt of salary, it is necessary for the technique in determining the employee’s salary permanent and Contract employees. One technique that can be used are Using K-Means Clustering Algorithm.